Komposisi Komunitas Serangga Aphidophaga dan Coccidophaga pada Agroekosistem Kacang Panjang (Vigna sinensis l.) di Kabupaten Garut - Lindung Tri Puspasari; Martua Suhunan Sianipar; Sri Hartati (Fakultas Pertanian Universitas Padjadjaran, 2016)
ABSTRACTComposition of Aphidophaga and Coccidophaga Insect Communities on Long Bean Agroecosystem (Vigna sismensis L.) at Garut RegencyThe research about Aphidophaga and Coccidophaga insect composition comunity on long beans (Vigna sinensis L.) agroecosystems was done in the month of April to November 2011 in Haruman Village, Leles District, Garut Regency. Research was conducted in the form of surveys which were done by collecting insects directly and using various traps ie yellow traps board, fitfall traps, and nets swinging. The dominant insect pest that found was Aphis craccivora which causing percentage of damage to the plants ranging from 20% to 90%. Types of aphidophaga and coccidophaga found were belong to the Order of Coleoptera : Family Coccinellidae Menochilus sexmaculatus, Micraspis sp., Harmonia sp., Verania lineata, Curinus coeruleus, Scymnus sp., Coccinella transversalis); the Order of Diptera : Family Syrphidae namely Ischiodon scutellaris; Neuroptera: Family Hemerobiidae; the Order of Diptera : Family Cecidomyiidae Aphidoletes aphidimyza; and there was also Carabidae beetles of the Order Coleoptera with species diversity index wasl relatively low. The highest abundance of predators of coccidophaga and aphidophaga group was dominated by Ischiodon scutellaris and Menochilus sexmaculatus.Key words: Diversity, Abundance, Dominant species, Insect pestsABSTRAKPenelitian mengenai komposisi komunitas serangga aphidophaga dan coccidophaga pada Agroekosistem kacang panjang (Vigna sinensis (L.) telah dilaksanakan pada Bulan April–November 2011 di Desa Haruman Kecamatan Leles Kabupaten Garut. Penelitian dilakukan menggunakan metode survei dengan mengoleksi serangga secara langsung, dan menggunakan berbagai perangkap antara lain perangkap papan kuning, fitfall trap, dan jaring ayun. Serangga hama dominan yang ditemukan adalah Aphis craccivora dengan persentase serangan berkisar 20% - 90%. Jenis aphidophaga dan coccidophaga lain yang ditemukan yaitu dari Ordo Coleoptera : Famili Coccinellidae: Menochilus sexmaculatus, Micraspis sp., Harmonia sp., Verania lineata, Curinus coeruleus, Scymnus sp., Coccinella transversalis; Ordo Diptera : Famili Syrphidae yaitu Ischiodon scutellaris; Neuroptera : Famili Hemerobiidae; Ordo Diptera : Famili Cecidomyiidae Aphidoletes aphidimyza; serta terdapat pula kumbang Carabidae dari Ordo Coleoptera dengan indeks keragaman spesies yang masih tergolong rendah. Kelimpahan tertinggi predator dari kelompok aphidophaga dan coccidophaga didominasi oleh spesies Ischiodon scutellaris dan Menochilus sexmaculatus.Kata kunci : Keragaman, Kelimpahan, Spesies dominan, Serangga hama